2004
DOI: 10.1080/09297040490911014
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-Spatial Working Memory Span: A Sensitive Measure of Cognitive Deficits in Children With ADHD

Abstract: Working memory (WM) has been hypothesised to be impaired in attention-deficit/hyperactivity disorder (ADHD). However, there are few studies reported on tests measuring visuo-spatial WM (VSWM) in ADHD. Some of these studies used paradigms including episodic memory, others only used low memory loads. In the present study we used a VSWM test that has not been used previously in ADHD research. The sensitivity of the VSWM test and a choice reaction time (CRT) test was evaluated in a pilot study by comparing them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Working memory is the ability to maintain and manipulate information relevant for the task at hand (Baddeley, 1981). Executive functions like working memory are considered essential for performing goal-oriented behaviors, and SWM deficits have been associated with behavioral disorders in children such as autism and attention deficit/hyperactivity disorder (ADHD) (Corbett, Constantine, Hendren, Rocke, & Ozonoff, 2009;Goldberg et al, 2005;Westerberg, Hirvikoski, Forssberg, & Klingberg, 2004). Studies of SWM have consistently implicated several brain regions as contributing to on-line maintenance and manipulation of spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…Working memory is the ability to maintain and manipulate information relevant for the task at hand (Baddeley, 1981). Executive functions like working memory are considered essential for performing goal-oriented behaviors, and SWM deficits have been associated with behavioral disorders in children such as autism and attention deficit/hyperactivity disorder (ADHD) (Corbett, Constantine, Hendren, Rocke, & Ozonoff, 2009;Goldberg et al, 2005;Westerberg, Hirvikoski, Forssberg, & Klingberg, 2004). Studies of SWM have consistently implicated several brain regions as contributing to on-line maintenance and manipulation of spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…Although ADHD per se does not imply generalized cognitive impairment Visual fields in children with attention-deficit ⁄ hyperactivity disorder before and after treatment with stimulants (Shue & Douglas 1992;Aron et al 2003;Clark et al 2007), it is associated with different dysfunctions and abnormalities of the central nervous system (CNS). It has also been suggested that impaired visuo)spatial working memory is a major component of ADHD (Westerberg et al 2004). The disorder is treated with stimulant medication when rehabilitation and other support measures are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…ADHD related visual-spatial working memory deficits tend to become more pronounced with increased task difficulty (Young et al, 2007) and may be associated with dysfunction in right prefrontal cortex brain regions (Clark et al, 2007). Although some researchers believe that spatial working memory impairments are secondary to the difficulties with inhibitory control that are often associated with ADHD (Ross, Harris, Olincy, & Radant, 2000), others view the spatial working memory deficit as a primary problem (Westerberg, Hirvikoski, Forssberg, & Klingberg, 2004).…”
mentioning
confidence: 99%